Cognitive structures of Iranian senior tourists towards domestic tourism destinations: A means-end chain approach. (June 2019) - Pezeshki, Fereshteh; Ardekani, Saeid Saeida; Khodadadi, Masood; Alhosseini Almodarresi, Seyed Mahdi; Hosseini, Faride Sadat
Abstract: This study constructed a hierarchical value map (HVM) which specified how Iranian senior tourists linked various attributes of domestic tourism destinations to definite consequences, and how such consequences helped them to satisfy their individual values. To do so, the present study, for the first time, demonstrated the cognitive structure of destination image on more abstract levels using the means-end chain (MEC) approach. Through the laddering technique and in-depth interviews with 30 Iranian senior citizens (ISTs), the hierarchical value map of the Iranian senior tourists was constructed, as a result of which seven key MECs were identified. The investigation revealed 12 attributes, 11 consequences, and five values that the Iranian senior tourists wished to achieve. Given the shortage of qualitative studies dealing with senior tourists' behaviour, the findings of this study could serve as a key basis for the segmentation of the senior tourism market and the formulation of destination positioning strategies in Iran.